Triggering Demand‒Side‒Management: Correlation of electricity prices, share of renewables, CO2‒contents, and grid‒frequency in the German electricity grid. - Krauter, Stefan; Zhang, L. (Proceedings of the 37th European Photovoltaic Solar Energy Conference, 07 - 11 September 2020.)
To provide a simple instrument to operate residential Load-Shifting or Demand-Side-Management systems, the measurement of the actual grid frequency seems to be an appropriate method. Due to the present inflexibility and the lack of sufficient throttling capabilities of lignite and nuclear power plants, a surplus of electricity generation occurs during periods of high wind and solar power generation. While the specific CO2- emission is decreasing then ‒ due to the increased share of Renewables, the grid frequency is increasing (to a certain limit). Using the grid frequency as an indicator to switch-on and off certain loads (loads that do not require power permanently (e.g. dishwashers, washing machines, dryers, fridges and freezers, heaters) could provide a simple, inexpensive demand-side management indicator to lower specific CO2‒emssions and costs (if a dynamic consumption tariff is available). To check the truthfulness of that hypothesis, the grid and frequency data of the German grid of the year 2018 have been collected and a the correlation between grid frequency, power surplus, share of renewables vs. CO2-contents and price at the European energy exchange (EEX) have been calculated. The results show: Correlation between frequency and share of renewables is quite low (r = 0.155) due to the fact that primary grid control quickly compensates deviations from the 50 Hz nominal frequency. There is a good anti-correlation (r = - 0.687) between the EEX‒prices and the share of renewables in the grid. Over the years, correlation between electricity trading prices (EEX) and CO2 emissions is quite good (r =0.665), within the one year (2018) that correlation almost doesn’t exist, possibly due to the inflexibility of the bulky lignite power plants that even operate at negative prices.
Keywords: Keywords: Load-Shifting; Demand-Side-Management; DSM; grid frequency; EEX; electricity trading prices; renewable share; flexibility; emissions; CO2

Correlation of grid-frequency, electricity prices, share of Renewables and CO2-contents of German electricity grid to enable inexpensive triggering of Demand-Side-Management - Krauter, Stefan; Zhang, L. (Proceedings of the 47th IEEE Photovoltaic Specialists Conference (PVSC 47) 2020)
Due to the present inflexibility and the lack of sufficient throttling capabilities of lignite and nuclear power plants, a surplus of electricity generation occurs during periods of high wind and solar power generation in the German electricity grid. While the specific CO2-emission is decreasing then - due to the increased share of Renewables, the grid frequency should be increasing (to a certain limit). Using the grid frequency as an indicator to switch-on and -off certain loads (loads that do not require power permanently (e.g. dishwashers, washing machines, dryers, fridges and freezers, heaters) could provide a simple, inexpensive demand-side-management indicator to lower specific CO2-emissions and costs (if a dynamic consumption tariff is applied). To check the truthfulness of that hypothesis, the grid and frequency data of the German grid of the year 2018 have been collected and the correlations between grid frequency, share of renewables, CO2-contents, and actual price at the European energy exchange (EEX) have been calculated. The results show: Correlation between grid frequency and the share of renewables is quite low (r=0.155) due to the fact that primary grid control quickly compensates deviations from the 50 Hz nominal frequency. As expected, there is a good anti-correlation (r=-0.687) between the EEX-prices and the share of renewables in the grid. Over the years, correlation between electricity trading prices (EEX) and CO2 emissions is quite good (r=0.665), within the one year (2018) that correlation almost doesn't exist, possibly due to the inflexibility of the bulky lignite baseload power plants that even operate at negative prices.
Keywords: CO2; EEX; Grid frequency; DSM; electricity price; Renewable share

Minimizing storage costs by substituting centralized electrical storage by thermal storage at the end user, also suppling balancing power for grid operation - Krauter, Stefan; Prior, Dirk (Energy Procedia)
Many processes in industrial and domestic applications require heating or cooling at certain steps of a process. Even if the process itself cannot be shifted towards periods of high PV output (which would be favorable), the heating and cooling necessities can be carried out via an inexpensive thermal storage instead of a costly electrical storage. Examples are: distillation units, washing machines, dishwashers, coolers, freezers. The resulting “shiftability” of power consumption can be a business model by offering that availability of load dispatching on the balancing power market. An example using PCM as cooling storage for refrigerators that has been investigated: A focus of this paper is the use of that load shifting ability to provide balancing power. Another emphasis is on the protection of individual consumer data: To keep the state of use of each individual consumer (actually: interactive consumer or “prosumer”) anonymous, but still performing the sales of balancing power, the orders for load-dispatching can be transmitted via transmitted via a regional, non-individual broadcasting message within the GSM network. Demonstrating DSMs capacities, abilities and limits concerning domestic applications is an important task to prepare large-scale implementation and to convince stakeholders. To reaching that goal, several realistic DSM scenarios for cooling applications and freezers have been developed with the prerequisite that DSM activities are supposed to be without comfort losses and without restrictions for consumers while the limits for lower and upper temperature for food are maintained.
Keywords: DSM; load management; load shifting; PCM; thermal storage; balancing power